Performance of indigenous yeasts in the processing of Chinese strong‐flavoured liquor during spontaneous mixed solid‐state or submerged fermentation. Issue 2 (21st March 2015) - You, Ling; Wang, Tao; Yang, Zhirong; Feng, Su
Abstract : To explore the in situ metabolic characteristics of yeasts involved in the spontaneous fermentation process of Chinese strong‐flavoured liquor, a comparison was conducted between solid‐state fermentation (SSF) and submerged fermentation (SmF) when supplemented with 24 indigenous yeast strains, with a focus on the production of ethanol and a broad range of volatile compounds responsible for the characteristics of Chinese strong‐flavoured liquor. Under the various experimental conditions, the 24 indigenous yeast strains showed different influences on the mixed fermentation system. The fluctuations caused by different yeast strains in the mixed system were less than those caused by the different fermentation modes relative to the formation of flavour compounds. SSF was found to be more suitable for the production of ethanol, methanol and ethyl lactate, whereas SmF was more suitable for the production of 10 higher alcohols, four esters and four acids. This study revealed the relationships amongst the indigenous yeasts, SSF, and the distinctive flavour profiles of Chinese strong‐flavoured liquor. This work provides evidence of the existence of internal stability in spontaneous SSF, thereby facilitating a better understanding of the fermentative mechanism in the SSF process for Chinese strong‐flavoured liquor production Copyright © 2015 The Institute of Brewing & Distilling